2018
DOI: 10.12659/msm.908218
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Visual Impairment in Adults in Binhu District, Wuxi, China

Abstract: BackgroundPreviously reported data has guided the treatment and prevention of blindness. This study aimed to evaluate the current prevalence and causes of visual impairment among adults who were 50 years old and older in the Binhu District of Wuxi City, China.Material/MethodsA randomized sample of stratified clusters was used to analyze individuals from 30 basic sampling units in Wuxi Binhu District. Visual impairment was defined according to World Health Organization (WHO) standards.ResultsA total of 6725 peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
6
10
1
Order By: Relevance
“…It was the leading cause of low vision and blindness in the younger group (aged 18–49 years), accounting for 58.97% of visual impairment, 59.45% of low vision and 50.00% of blindness. These findings were consistent with previous studies in China (Saw et al 2004; Zhang et al 2012; Li et al 2012; Wang et al 2013; Tang et al 2015; Li et al 2015; Yang et al 2016; Zhang et al 2016; Guo et al 2017; Li et al 2018; Chen et al 2018). Refractive error/amblyopia is not an age‐related eye disorder, and its substantial contribution to the burden of visual impairment in the younger group may reflect a high prevalence in younger working‐aged Chinese in whom the disability burden is likely to be greater due to impediments to occupational function.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It was the leading cause of low vision and blindness in the younger group (aged 18–49 years), accounting for 58.97% of visual impairment, 59.45% of low vision and 50.00% of blindness. These findings were consistent with previous studies in China (Saw et al 2004; Zhang et al 2012; Li et al 2012; Wang et al 2013; Tang et al 2015; Li et al 2015; Yang et al 2016; Zhang et al 2016; Guo et al 2017; Li et al 2018; Chen et al 2018). Refractive error/amblyopia is not an age‐related eye disorder, and its substantial contribution to the burden of visual impairment in the younger group may reflect a high prevalence in younger working‐aged Chinese in whom the disability burden is likely to be greater due to impediments to occupational function.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, an increasing trend of low vision prevalence was also observed in the Taizhou Eye study (Tang et al 2015) and the Nine‐Province Eye study (Zhao et al 2018). In our study, we also confirmed that the prevalence of low vision and blindness increased with age (Saw et al 2004; Li et al 2012; Tang et al 2015; Li et al 2015; Yang et al 2016; Zhang et al 2016; Guo et al 2017; Hu et al 2017; Chen et al 2018). We observed a higher likelihood of visual impairment and low vision in women than men, which was also found in the China Nine‐Province Survey (Zhao et al 2018) and the Wuxi Eye study (Chen et al 2018).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations